PERBAIKAN KUALITAS AIR KOLAM BUDIDAYA IKAN DENGAN SISTEM FILTRASI DI KECAMATAN BAKUMPAI BARITO KUALA KALIMANTAN SELATAN - Dini Sofarini; Yunandar Yunandar; Rina Nurhidayah (Universitas Mataram, 2022)
The filtration system is a technique for improving the water quality of fish farming ponds due to low productivity from swamp water sources and the Barito Marabahan river. The pollution comes from anthropogenic activities, leftover feed, and fish feces. Accumulating feces, leftover feed, and waste metabolites cause a decrease in water quality, especially from the parameter values of water pH and ammonia levels during rearing. High ammonia can cause poisoning or lack of oxygen and accelerate the development of the disease. The purpose of this community service activity is to improve the quality of fish pond water, especially the water pH parameters. It is used for recirculation-based commercial fish enlargement activities, local materials, swamps water, and river water resources. The methods used in this activity range from the steps of site surveys, program socialization, counseling, and the creation of filtration units. This activity was carried out from June to August 2022, located at the Pendalaman Baru fish cultivator group (Pokdakan), Barambai District, Barito Kuala Regency. The success rate in training on manufacturing and maintaining recirculating units with portable filters is 80%. The evaluation results using the scoring technique stated that the partner's knowledge level increased by 80% for the manufacture of filtration units and their installation, an adaptation of filtration unit designs increased by 85%, and the unit was operational. Maintenance techniques and scheduling of fish feeding increased by 70%. The rate of sedimentation originating from rivers and swamps is the primary water source for aquaculture activities that enter the pond inlet pipe. The material accumulates in the filtration unit with a specific thickness, thus requiring more intensive maintenance for fish pond cultivating groups. This technique can be developed as an initial treatment to improve water quality in various fish pond ecosystems that utilize other water sources.